The Sicilian inheritance : a novel [large type] - Piazza, Jo (Random House Large Print, 2024)
"Sara Marsala barely knows who she is anymore after the failure of her business and marriage. On top of that, her beloved great-aunt Rosie passes away, leaving Sara bereft with grief. But Aunt Rosie's death also opens an escape from her life and a window into the past by way of a plane ticket to Sicily, a deed to a possibly valuable plot of land, and a bombshell family secret. Rosie believes Sara's great-grandmother Serafina, the family matriarch who was left behind while her husband worked in America, didn't die of illness as family lore has it . . . she was murdered. Thus begins a twist-filled adventure that takes Sara all over the picturesque Italian countryside as she races to solve a mystery and prove her birthright. Flashing back to the past, we meet Serafina, a feisty and headstrong young woman in the early 1900s thrust into motherhood in her teens, who fought for a better life not just for herself but for all the women of her small village. Unsurprisingly it isn't long before a woman challenging the status quo finds herself in danger. As Sara discovers more about Serafina she also realizes she is coming head-to-head with the same menacing forces that took down her great-grandmother. At once an immersive multigenerational mystery and an ode to the undaunted heroism of everyday women, The Sicilian Inheritance is an atmospheric, page-turning delight"--